Network typology and international opportunity recognition: Moderating role of entrepreneurial orientation - Sahar Ahmadian; Somayeh Abdolmaleki (Journal of Global Entrepreneurship Research, 2018)
International entrepreneurship (IE) is fundamentally captured in the identification and exploitation of opportunities for international exchange. Yet little is known about the methods used by entrepreneurs for opportunity recognition. Previous work on IE emphasizes the importance of social networks for identifying opportunities in foreign markets. While business network and institutional network are less studied in previous studies, this paper aims to examine the effect of social, business, and institutional network on international opportunity recognition with the moderating role of entrepreneurial orientation. By applying network based theory to the analysis of 150 Iranians SMEs, the result indicates that; social network, business network, and institutional network positively affect international opportunities recognition. Furthermore the results show that entrepreneurial orientation moderated the effect of business, and institutional network on international opportunity recognition. While the moderating role of entrepreneurial orientation in the effect of social network on international opportunity recognition, is not supported.
Keywords: 650; Network typology; International opportunity recognition; Entrepreneurial orientation